Pengaruh Dexmedetomidine Intravena terhadap Kadar Superoxide Dismutase 1 (Sod-1) Hepar Kelinci pada Hepatic Ischemic Reperfusion Injury Model - Kuncoro, Dodhi; Noviasari, Nina Anggraeni; Istiqomah, Istiqomah; Muslimah, Muslimah; Basuki, Rochman (Syntax Literate, 2025)
Ischemic Reperfusion Injury is a state where there is cellular damage as a result of organ hypoxia are accompanied by improved delivery oksigen.Cedera after ischemia reperfusion marked with an oxidant production, complement activation, leukocyte endothelial cell adhesion, platelet aggregation of leukocytes, increased microvascular permeability and a decrease in the endothelium relaxation dependent.Enzym ie superoxide scavenging superoxide dismutase (SOD), plays a role in protecting the organ from organ damage due to ischemia-reperfusion injury.Hepar is the organ most in producing superoxide dismutase (SOD-1)as a result of injury after ischemic reperfusion. To determine the effect of intravenous dexmedetomidine on levels of superoxide dismutase 1 (SOD-1) rabbit liver in hepatic ischemic reperfusion injury. Methods, An experimental study Randomize Post Test Only Control Group Design uses 10 New Zealand rabbits. 5 rabbits given the form of dexmedetomidine treatment of 0.5 mcg / kg / h and performed occlusion of the portal vein hepatica (K1). 5 rabbits untreated (KK) also performed hepatic portal vein occlusion and examination superoxide dismutase 1 (SOD-1) as a control. Shapiro Wilk normality test and parametric tests using independent t-test. Results, The mean levels of SOD-1 group konrol 0.54 ± 0.24 and a P value of 0.76 (normal) and average levels of SOD-1 in the treatment group 1.22 ± 0.43 and a P value of 0.129 (normal).Uji parametric test with Independent t-test available p = 0,017.Because value of p <0.05, we conclude there is a significant difference. Conclusion, Dexmedetomidine significantly increase the value of superoxide dismutase 1 (SOD-1) in rabbits given new zealand treatment of occlusion of the hepatic portal vein.